A teoria da justiça distributiva em Anarquia, Estado e Utopia de Robert Nozick - Cerqueira, Thiago de Amorim (2022)
What is the fair way to distribute goods and rights to individuals in society? The question of distributive justice is one of the central problems of political philosophy. In this work, we analyze one of the theories of distributive justice offered in response to the question raised above. The philosopher Robert Nozick develops in Anarchy, State and Utopia, one of the most recognized theories of distributive justice, since John Rawls, the theory of entitlement. As his presuppositions, Nozick returns to the analysis of the state of nature, and asks himself, initially: is the state necessary? Is it possible to offer solutions to the inconveniences of the state of nature without having to create the state? For Nozick, the State is continually interfering with the individual freedom of its citizens, most often the result of standardized theories of justice. For Nozick, the determination of distributive justice principles based on standardized criteria that takes into account only what a person has or does not have at a given moment, ends up violating people's individual freedom. Contrary to standardized theories of justice, Nozick proposes a theory of justice that dispenses with analyzes of standardized and fixed criteria, such as equality, for example, to theorize a historical analysis of justice that takes into account the history behind each current distribution. For him, determining the fair distribution of society's benefits depends on a historical analysis of how they happened in the past. For the arguments in defense of the historical theory of entitlement, Nozick uses the thesis of self-ownership, the conception of natural rights, and the formulation of the second Kantian imperative of never using people's humanity as a means, but always as an end in itself.